Transcatheter closure of persistent ductus arteriosus with the Amplatzer duct occluder in very young symptomatic children. Issue 12 (16th November 2004) - Butera, G; De Rosa, G; Chessa, M; Piazza, L; Delogu, A; Frigiola, A; Carminati, M
Abstract : Objectives: To analyse safety, efficacy, and follow up results of percutaneous closure of persistent ductus arteriosus (PDA) in very young symptomatic children. Patients and design: Between March 2000 and March 2003, of 197 patients treated at the authors' institution 18 were symptomatic children aged ⩽ 3 years old. Seven of these children were ⩽ 1 year old. Indications for closure were failure to thrive (12 patients) and frequent respiratory infections (six patients). The procedure was carried out under heavy sedation with fluoroscopic control. The Amplatzer duct occluder device was used. Basal physical examinations and echocardiograms were performed before the procedure and at follow up (three, six, and 12 months and yearly thereafter). Results: Mean (SD) age was 18.3 (10) months and mean (SD) weight at closure was 9.1 (2.2) kg. Neither death nor any major complications occurred. Complications occurred in three patients aged ⩽ 1 year. Two patients had a mild inguinal haematoma. One patient had femoral artery thrombosis that was successfully treated by intravenous urokinase. The mean (SD) follow up was 12.8 (8.5) months. No problems occurred. Patients with recurrent respiratory infections had no significant recurrences and children who had failed to thrive had significantly increased growth. Conclusions: In experienced hands, percutaneous closure of moderate to large PDA in very young symptomatic children is safe, effectively closes the PDA, and solves clinical problems.